Multiple myeloma simulating olfactory sulcus meningioma: case report and review of the literature - Mosquera, Dilia; Carballo, Leandro; Baldoncini, Matías; Echavarría, Mickaela (Revista Argentina de Neurocirugía, 2025)
Introduction: central nervous system involvement by multiple myeloma is extremely rare and is diagnosed in less than 1% of cases. Differential diagnosis should be made with lymphomas, metastases, sarcomas, osteochondromas, hemangiopericytomas, infectious meningitis or meningiomas. Objective: to report an unusual case of a giant brain space occupying lesion simulating a meningioma of the olfactory sulcus. Case description: 46-year-old female patient with a history of multiple myeloma in apparent remission after autologous bone marrow transplantation, who consulted for a palpable mass in the frontal region associated with holocranial headache of intensity 7/10 and decreased visual acuity of two months of evolution with imaging studies compatible with olfactory sulcus meningioma. Intervention: craniotomy and total resection of the lesion by bicoronal approach. Histological sections showed a neoplastic proliferation consisting of cells with a spherical nucleus and lateralized eosinophilic cytoplasm. CD 138 +++ at membrane level. Lesion compatible with involvement of the central nervous system by multiple myeloma. Conclusion: the unusual finding of this pathology offers challenges in the preoperative imaging diagnosis due to the great similarities with other neoplasms, mainly meningiomas, so it is important to consider it as a differential diagnosis.